Five Decades Later, Are Mesenchymal Stem Cells Still Relevant? - Gomez-Salazar, Mario; Gonzalez-Galofre, Zaniah N.; Casamitjana, Joan; Crisan, Mihaela; James, Aaron W.; Péault, Bruno (Frontiers in Bioengineering and Biotechnology, 2020)
Mesenchymal stem cells are culture-derived mesodermal progenitors isolatable from all vascularized tissues. In spite of multiple fundamental, pre-clinical and clinical studies, the native identity and role in tissue repair of MSCs have long remained elusive, and MSC selection in vitro from total cell suspensions essentially unchanged, as a mere primary culture, for half a century. Recent investigations have helped understand the tissue origin of these progenitor cells, and uncover MSC alternative effects on tissue healing via growth factor secretion and interaction with the immune system. In this review, we describe current trends in MSC biology and discuss how these may improve the use of these therapeutic cells in tissue engineering and regenerative medicine.